Electron holes in the outer radiation belt: Characteristics and their role in electron energization. Issue 1 (3rd January 2017) - Vasko, I. Y.; Agapitov, O. V.; Mozer, F. S.; Artemyev, A. V.; Drake, J. F.; Kuzichev, I. V.
Abstract: Van Allen Probes have detected electron holes (EHs) around injection fronts in the outer radiation belt. Presumably generated near equator, EHs propagate to higher latitudes potentially resulting in energization of electrons trapped within EHs. This process has been recently shown to provide electrons with energies up to several tens of keV and requires EH propagation up to rather high latitudes. We have analyzed more than 100 EHs observed around a particular injection to determine their kinetic structure and potential energy sources supporting the energization of trapped electrons. EHs propagate with velocities from 1000 to 20, 000 km/s (a few times larger than the thermal velocity of the coldest background electron population). The parallel scale of observed EHs is from 0.3 to 3 km that is of the order of hundred Debye lengths. The perpendicular to parallel scale ratio is larger than one in a qualitative agreement with the theoretical scaling relation. The amplitudes of EH electrostatic potentials are generally below 100 V. We determine the properties of the electron population trapped within EHs by making use of the Bernstein‐Green‐Kruskal analysis and via analysis of EH magnetic field signatures. The density of the trapped electron population is on average 20% of the background electron density. The perpendicular temperature of the trapped population is on average 300 eV and is larger for faster EHs. We show that energy losses of untrapped electrons scattered by EHs in the inhomogeneous background magnetic field may balance the energization of trapped electrons. Key Points: We perform statistical study of properties of electron holes observed around one injections front in the outer radiation belt We determine properties of trapped electron population via BGK approach and via analysis of electron hole magnetic field signatures Electron holes may energize trapped electrons at expense of energy loss of untrapped electrons as they propagate toward higher latitudes